Spacing between plants and cultivar affect the production componentes of Italian zucchini - Leilson C. Grangeiro; Carlos J. X. Cordeiro; Valdivia de F. L. Sousa; Jandeilson P. Santos; Francisco I. Souza; Nubia M. Ferreira (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The italian zucchini is a vegetable of national importance, much appreciated, which requires techniques that aim to increase production in less space. Plant spacing can influence the development of plants and the fruit production. The objective of this study was to evaluate the performance of Italian zucchini cultivars as a function of plant spacing. The experimental design was a randomized blocks in a 2 x 4 factorial scheme with four repetitions. The treatments consisted of a combination of two cultivars of zucchini (Alícia and Caserta) and four spacings between plants (0.4, 0.5, 0.6 and 0.7 m). The evaluated characteristics were: total number of fruits plant-1, number of commercial fruits plant-1, total productivity, commercial and non commercial, fresh mass of commercial fruits and dry mass of the plant. The cultivars responded differently to spacings between plants. The Alicia hybrid showed higher commercial yield, 28,490.5 kg ha-1 at spacing of 0.64 m between plants and Caserta cultivar, 26,398.8 kg ha-1 at spacing of 0.4 m.